Capacity Development and Creating Opportunities for the Elderly through the Cultural Capital Process of the Four Ethnic Groups in Si Sa Ket Province - Buachthaisong, Sitthichai; Jaikorn, Thiwaporn (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The objectives of this research were 1) to study the development of roles and potential of the elderly in culture and tradition and the model of the elderly in Si Sa Ket Province, 2) to construct the model of capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province, 3) to evaluate the propriety, feasibility, utility, and accuracy of the model of capacity development in terms of culture and tradition in Si Sa KET Province. The research was conducted in 3 phases. Phase 1: Studying related theoretical concepts, the context, capacity development, and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province and the model of the elderly together with studying related documents and research consisted of 3 steps as follows: 1) studied and analyzed documents regarding concepts, theories, and related research work, 2) conducted field research to study the context by groups discussion consisting of 60 seniors and community leaders using a group discussion format, and 3) conducted in-depth interviewed with the 290 elderly and people involved in the elderly work using the interview form. Phase 2: Building the model of capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province consisted of 3 steps as follows: 1) drafted the format and the guide for capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province, 2) evaluated the model of capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province by 15 experts using the model evaluation form and analyzed data by frequency, percentage, mean, and standard deviation, as well as the propriety, feasibility, utility, and accuracy, and 3) improved the draft of the model for capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket province as recommended by experts. Phase 3: Evaluating the model of capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket Province from 20 stakeholders used the model evaluation form and frequency, percentage, mean, and standard deviation, as well as the feasibility, propriety, utility, and accuracy for data analysis. The findings were as follows. 1) The key components of the capacity development and creating opportunities for the elderly through the cultural capital process of the four ethnic in Si Sa Ket Province consisted of the basic skills necessary for learning, community development work, and the participation and coexistence in society. 2) The application of the model to the elderly model consisted of lectures/training, interviews/group discussions, and role-play activities. 3) The model evaluation were the basic learning skills of the elderly model, the ability to work in the community development of the senior model, and the participation and coexistence of the elderly model society. The model evaluation revealed that feasibility, propriety, and utility were at the highest level, while the accuracy was at a high level.